Зависимость размеров блоков электролитического серебра от перенапряжения разряда его комплексных ионов - Берсирова, О.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
The correlation between nanocrystal’s sizes of silver coatings deposited from solutions of the coordinate compounds of silver (I) [Ag(CN)2(SCN)2]^3−, [Ag(CN)3]^2− and the [Ag(CN)2]^−, and the overpotential of an electrochemical reaction is discussed. The dependence of grain’s size of silver deposits on the general polarization has characteristic minimum at −0.5 V. This value doesn’t depend on the nature of a silver electroactive complex.